LANGUAGE ATTITUDE OF THE TADJIMALELA EXTRACURRICULAR GROUP AT STATE JUNIOR HIGH SCHOOL 8 BANDUNG TOWARDS SUNDANESE LANGUAGE: A SOCIOLINGISTIC STUDY: SIKAP BAHASA KELOMPOK EKSTRAKURIKULER TADJIMALELA DI SEKOLAH MENENGAH PERTAMA NEGERI 8 BANDUNG TERHADAP BAHASA SUNDA: KAJIAN SOSIOLINGISTIK - Ranti Julita; Wahya Wahya; Hera Meganova Lyra (LLDIKTI Wilayah X, 2023)
This study aims to describe the attitudes of teenagers towards the Sundanese language within the Tadjimalela extracurricular group at State Junior High School 8 Bandung. This research employs a qualitative descriptive approach with teenagers who participate in the Tadjimalela extracurricular activity as the subjects. Data collection techniques include observation, questionnaires, interviews, and persona triangulation. The analysis technique utilized is the interactive model of qualitative data analysis by Miles et al. The research findings indicate that teenagers engaged in the Tadjimalela extracurricular activity exhibit a positive attitude towards the Sundanese language. This is evident through their pride in Sundanese culture and language, as well as their commitment to using the Sundanese language despite a limited awareness of linguistic norms among teenagers.